Assessing the Ovarian Accessory Glands to Determine the Parity of Phlebotomus papatasi, Vector of Zoonotic Cutaneous Leishmaniasis, under Laboratory Condition - Fatemi, Mahboubeh (J Arthropod Borne Dis, 2017)
BACKGROUND: Zoonotic cutaneous leishmaniasis (ZCL) is a neglected tropical disease prevailed in many rural areas of 17 out of 31 provinces in Iran. The main vector of the disease is Phlebotomus papatasi and the causative agent is Leishmania major in ZCL foci of Iran. In the current study we investigated the validity of accessory glands secretions as an indicator to recognize parous from nulliparous Ph. papatasi females under laboratory conditions. METHODS: Over 235 laboratory-reared females of Ph. papatasi were dissected in 6 groups including: newly emerged, one hour, one day, two days, and three days after blood feeding and also after oviposition under stereo microscope for their parity in 2014–2015. RESULTS: Transparent glands were compatible with nulliparous only in newly emerged sand flies. In sand flies dissected after oviposition, accessory glands were rather large as a result of oviposition though they were transparent. CONCLUSION: The accessory glands secretions could not be as an indicator for distinguishing parous from nulliparous of Ph. papatasi females.